The diaries of John Gregory Bourke. - Bourke, John Gregory, 1846-1896 (University of North Texas, 2005)
John Gregory Bourke kept a monumental set of diaries as aide-de-camp to Brigadier General George Crook. This second volume opens as Crook prepares for the expedition that would lead to his infamous and devastating Horse Meat March. It continues with the Powder River Expedition and ends with a retrospective of his service in Tucson, Arizona.